Synthesis of a 3D Porous Multicomponent Bioceramic Scaffold - Sari, Yessie Widya; Munir, Ryaas Mishbachul; Saputra, Angga; Sari, Mona; Aminatun; Suciati, Tri; Mohamad, Che Wan Sharifah Robiah; Gunawarman; Yusuf, Yusril (Research Center of Inorganic Materials and Coordination Complexes, FMIPA Universitas Sriwijaya, 2024)
In this study, 3D porous multicomponent bioceramic scaffolds were fabricated. Hydroxyapatite (HA) and carbonate-substituted hydroxyapatite (CHA) synthesized from Asian moon scallop shell (Amusium pleuronectes) served as the bioceramics, whereas alginate and chitosan served as the polymeric components. The study was focused on determining whether the presence of polyvinyl alcohol (PVA) in the scaffold exerted an impact. When PVA was not included, the morphological examination revealed that the samples exhibited porous structures characterized by effective pore interconnectivity and a substantial pore size. X-ray diffraction and scanning electron microscopic analyses indicated that the inclusion of PVA led to a decrease in the crystallinity, pore size, and porosity of the scaffolds. Those containing PVA exhibited porosity levels in the range of 56%–60%, and pore sizes ranged from 42 to 90 µm. These properties may provide advantages for the scaffold with respect to the ability for cell migration and cell attachment, thus enhancing new bone formation. Moreover, the compositions of HA and chemically modified HA (CHA) within the scaffold influenced the crystallinity and uniformity of the scaffold morphology. This finding suggests the potential for crafting a customized porous bioceramic scaffold based on specific compositions.